2021
DOI: 10.1002/onco.13804
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Alpelisib + Fulvestrant Compared with Real-World Standard Treatment Among Patients with HR+, HER2–, PIK3CA-Mutated Breast Cancer

Abstract: Background. The BYLieve trial (NCT03056755) confirmed efficacy and safety of alpelisib with fulvestrant for hormone receptor-positive (HR+), human epidermal growth factor receptor-2-negative (HER2À), PIK3CA-mutated advanced breast cancer (ABC), after cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) with an aromatase inhibitor (AI) as immediate prior therapy. Further analyses were performed to compare efficacy from BYLieve with effectiveness of standard treatment in the real-world setting. Patients and Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
2
20
1
2
Order By: Relevance
“…This method reduces confounding bias, while maintaining all patients in a weighted form in the analysis (except for trimmed cohorts), making it a more reasonable method than other propensity score techniques for balancing patient groups with small sample sizes. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…This method reduces confounding bias, while maintaining all patients in a weighted form in the analysis (except for trimmed cohorts), making it a more reasonable method than other propensity score techniques for balancing patient groups with small sample sizes. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…The PIK3CA mutations induce hyperactivation of the PI3K p110 subunit alpha isoform, thus leading to increased cell growth and proliferation. In the SOLAR-1 and BYLieve clinical trials, the synergistic effect of antitumor activity observed in alpelisib-fulvestrant combination therapy resulted in greater PFS, in contrast to usage of either alpelisib or fulvestrant as monotherapies [23,24]. Because approximately 40% of patients with HR-positive, HER2-negative breast cancer also have the PIK3CA mutation, alpelisib-fulvestrant is an effective therapeutic combination for targeted therapy, especially for cancers with endocrine resistance [22].…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%
“…Second-line treatment options include fulvestrant, cytotoxic chemotherapy, or anti-oestrogen therapy combined with inhibitors of the mammalian target of rapamycin (mTORi). Additionally, growing evidence supports the use of next-generation oral SERDs ( Table 2 ) and combinatorial strategies with alpha-selective phosphoinositide 3-kinase inhibitors (PI3Ki) in patients harbouring somatic, activating PIK3CA mutations [ 31 , 32 ]. The optimal sequencing of this repertoire of therapeutic strategies, however, remains the subject of ongoing clinical trials such as the SONIA study (ClinicalTrials.gov identifier NCT03425838), and the growing use of commercially available tissue and liquid biopsy-based companion diagnostic panels is leading to a surge in biomarker-driven treatment strategies post-CDK4/6-inhibitor therapy in ER+ metastatic breast cancer.…”
Section: Oestrogen Receptor Signallingmentioning
confidence: 99%